(3CLhHI GdTjN GHf SjfG Ydi CHj GdQjMGf GdHjQhfjs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s; (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI eSCdI eG eYfi GdYbd HGdbhJ aEf GdTF GdPi jOQc efG GdeYbhdGJ bO HGf Cfg eLQO Yf GdeGOI s
(3BNQgG (B:s
(3hGdeJYGdL GHJOGAg GdOjf hGdYbd ef GdaGYd ai GdZGdH dCLd GdZGjI dJMUjd GdUhQI hgPG BNQ eG cJH ai GdLhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs